Conscience Without a Map: The Disclosure Problem in Secular Institutional Refusal. - Stys, John C. (American Journal of Bioethics, 2026)
The article examines the concept of institutional conscience in healthcare, focusing on the challenges of applying secular institutional conscience alongside faith-based conscience protections. It highlights that while Catholic hospitals operate under clear, publicly accessible Ethical and Religious Directives, secular institutions lack comparable transparency and accountability frameworks, raising concerns about patient awareness of services refused on moral grounds. The discussion emphasizes practical issues such as inadequate disclosure to patients, difficulties families face when clinical conditions worsen unexpectedly, and the potential overlap between conscience-based refusals and financial incentives. To address these challenges, the article proposes a minimum infrastructure including clear point-of-care disclosures, pre-arranged transfer agreements, and accreditation-linked oversight to ensure institutional conscience rights are implemented transparently and consistently.